DETERMINANTS OF PREMARITAL SEXUAL BEHAVIOR AMONGST ADOLESCENTS IN INDONESIA - Nadhirul Mundhiro; Ridhwan Fauzi; Mohammad Ainul Maruf; Nurfadhilah Nurfadhilah (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Premarital sex is a growing social issue in Indonesia. The number of adolescents who conduct premarital sex has increased over the years. This study aimed to analyze the determinants of premarital sex behavior among adolescents in Indonesia. The study used secondary data from the 2017 Indonesian Demographic Health Survey (IDHS) with a total of 22,583 adolescent participants. The chi-square and multiple logistic regression were performed to assess the association of premarital sex behavior with socio-demographic status, tobacco, alcohol, and drug use. The results revealed that premarital sex was associated with sex, age, education level, smoking status, alcohol consumption, and drug use. Adolescents who had drunk alcohol were almost twenty times more likely (AOR = 19,888; 95% CI = 16,124-24,531) to have premarital sexual intercourse compared to adolescents who had not. The results found that premarital sex was strongly correlated with addictive substance use. Therefore, the government should formulate integrated health intervention programs to prevent risky health behaviors among adolescents. These can include integrating education on the dangers of smoking, alcohol consumption, and drugs into the Generation Planning or Generasi Berencana (GENRE) program, or Pusat Informasi dan Konseling Remaja (PIK R) or Youth Information and Counseling Center, which focuses on reproductive health in one package.